2011
DOI: 10.1098/rsbl.2011.0458
|View full text |Cite
|
Sign up to set email alerts
|

Long-term cleaner fish presence affects growth of a coral reef fish

Abstract: Cleaning behaviour is considered to be a classical example of mutualism. However, no studies, to our knowledge, have measured the benefits to clients in terms of growth. In the longest experimental study of its kind, over an 8 year period, cleaner fish Labroides dimidiatus were consistently removed from seven patch reefs (61 -285 m 2 ) and left undisturbed on nine control reefs, and the growth and parasite load of the damselfish Pomacentrus moluccensis determined. After 8 years, growth was reduced and parasiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
60
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 63 publications
(63 citation statements)
references
References 22 publications
3
60
0
Order By: Relevance
“…The cleaning mutualism involving the cleaner wrasse Labroides dimidiatus provides a model system to study cooperation in asymmetric games such as this: cleaners may cooperate with client fish by consuming their ectoparasites, leading to net benefits for clients [39,40] but preferentially exploit them by eating mucus [41], while non-predatory clients lack the option to cheat in return (they cannot eat a cleaner). Lacking the option to reciprocate, clients face the challenge of inducing cleaners to feed against their preference, in order to obtain a good cleaning service.…”
Section: Introductionmentioning
confidence: 99%
“…The cleaning mutualism involving the cleaner wrasse Labroides dimidiatus provides a model system to study cooperation in asymmetric games such as this: cleaners may cooperate with client fish by consuming their ectoparasites, leading to net benefits for clients [39,40] but preferentially exploit them by eating mucus [41], while non-predatory clients lack the option to cheat in return (they cannot eat a cleaner). Lacking the option to reciprocate, clients face the challenge of inducing cleaners to feed against their preference, in order to obtain a good cleaning service.…”
Section: Introductionmentioning
confidence: 99%
“…This relationship suggested that mobile reef fish actively seek cleaner wrasses in order to have gnathiids and other parasites removed. Clague et al (2011) showed that on reefs with cleaner fish, older P. moluccensis were larger at a certain age than those from reefs with no cleaner fish. They also found that copepod abundance was higher on fish from reefs with no cleaner fish, but only for larger host fish.…”
Section: Cleaning Mutualismmentioning
confidence: 99%
“…Clague et al (2011) showed that, on reefs with cleaner fish, older Pomacentrus moluccensis were larger at a certain age than those from reefs without cleaner fish. Gnathiids have been demonstrated to be important during settlement, in that a single gnathiid can decrease the success of settlement of P. amboinensis larvae significantly .…”
Section: Chapter 3 Presence Of Cleaner Wrasse Increases the Recruitmmentioning
confidence: 99%
See 2 more Smart Citations